Assessment of left ventricular myocardial work done by noninvasive pressure–strain loop technique in patients with essential hypertension - Jun Ding; Hong‐Guang Sun; Juan Liu; Dan Wu (Annals of Noninvasive Electrocardiology, 2022)
Abstract Objective To investigate the value of the noninvasive pressure–strain loop (PSL) technique for assessing left ventricular myocardial work done in patients with essential hypertension. Methods Prospectively, 60 patients with hypertension visiting the hospital from August 2020 to July 2021 were collected and divided into the mild hypertension group (SBP 140–159 mmHg, 35 cases) and the moderate‐to‐severe hypertension group (SBP ≥160 mmHg, 25 cases). Another 40 cases of healthy adults were collected as the control group. The differences in the global long‐axis strain (GLS) and peak strain dispersion (PSD) of the left ventricle, global work index (GWI), global constructive work (GCW), global wasted work (GWW), and global work efficiency (GWE) were compared among the three groups. The receiver operating characteristic curve was used to evaluate the PSD, GWI, GCW, and GWW. The myocardial work index (MWI) and MWI percentages in the apical, middle, and basal segments of the heart were also compared among the groups. Results (1) The PSD, GWI, GCW, and GWW were significantly different among the groups (Χ2 = 57.605, 79.203, 76.973, and 17.429, respectively, p < .05), while the GLS and GWE were not (Χ2 = 1.559 and 5.849, respectively, p > .05). (2) The GWI had the highest specificity (97.5%) and the GCW the highest sensitivity (95%) in predicting hypertension. The percentage of apical MWI gradually increased (F = 11.230, p < .05) and the percentage of basal MWI gradually decreased (F = 10.665, p < .05) from the control group to the mild hypertension group to the moderate‐to‐severe hypertension group; there was no significant difference in the percentage of mid‐MWI (F = 0.593, p > .05). Conclusions The noninvasive PSL technique could be used to assess myocardial work done in patients with essential hypertension.